Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2207746
|View full text |Cite
|
Sign up to set email alerts
|

EEG analysis of implicit human visual perception

Abstract: Image Based Rendering (IBR) allows interactive scene exploration from images alone. However, despite considerable development in the area, one of the main obstacles to better quality and more realistic visualizations is the occurrence of visually disagreeable artifacts. In this paper we present a methodology to map out the perception of IBR-typical artifacts. This work presents an alternative to traditional image and video quality evaluation methods by using an EEG device to determine the implicit visual proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…For the EEG data, ERPs were extracted as well as performing frequency analysis. For analysis of the ERPs [35], the data was extracted around the onset of the distortion. It could be shown that for artifacts that are on the moving part of the video (i.e.…”
Section: Spectral Analysismentioning
confidence: 99%
“…For the EEG data, ERPs were extracted as well as performing frequency analysis. For analysis of the ERPs [35], the data was extracted around the onset of the distortion. It could be shown that for artifacts that are on the moving part of the video (i.e.…”
Section: Spectral Analysismentioning
confidence: 99%
“…This body of work is particularly novel since, typically, EEG has not been used for complex or moving stimuli. In a 2012 study, we explored the possibility of detecting artifacts in video sequences with EEG [11]. The study measured the covert (implicit) visual processing associated with different types of artifacts.…”
Section: Video and Image Quality Assessment With Eegmentioning
confidence: 99%
“…The most relevant research has been done by Mustafa et al [2012] who looked at artifacts in videos and the corresponding EEG results. They showed the obvious brain response to artifacts in videos in the form of Event-Related Potentials (ERP's).…”
Section: Perception and Eegmentioning
confidence: 99%
“…Despite a substantial amount of research in applying perception to graphics and IBR [Vangorp et al 2011;Ferwerda et al 1996;Anderson et al 2011], only recently has there been a growing interest in using an EEG to analyze visual processing [Mustafa et al 2012;Lindemann and Magnor 2011;Rossion and Caharel 2011;Agam and Sekuler 2007]. Also, the use of an EEG in computer graphics research is now much easier with the advent of systems like the Emotiv EPOC neuroheadset [Emotiv 2012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation